Nanotechnology-Based Nanopolymeric Polyherbal Formulation for Enhanced Antioxidant and Anti-Glycation Activity - Astuti, Febriana; Mustofa; Arif Budi Setianto; Akrom (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Elevated oxidative stress and glycation give to the enhancement of degenerative condition such as diabetes and heart disease. Herbal extracts such as Apium graveolens, Centella asiatica, and Orthosiphon stamineus possess well-documented antioxidant and anti-glycation properties. However, their therapeutic effectiveness is measured by poor bioavailability, highlighting the need for innovative formulations. Nanotechnology presents a indicative of success approach by improving the solubility and distribution of active compounds. This study developed a nanopolymeric formulation by combining extracts of Apium graveolens, Centella asiatica, and Orthosiphon stamineus utilizing the ionic gelation method by chitosan, NaTPP, and Tween 80. The nanoparticles were characterized based on particle size, PDI, zeta capability, TEM, and FTIR. In vitro assays utilizing peripheral blood mononuclear cells (PBMCs) were conducted to analyze antioxidant activity through Nrf2 and GST expression, and anti-glycation capability by measuring AGEs. The nanopolyherbal particles had an average size of 186 ± 46.81 nm, by a PDI of 0.434 ± 0.04 and a zeta capability of -29.69 ± 1.54 mV. Both 1% and 3% nanopolyherbal treatments increased Nrf2 stages (66.77 ± 7.65 and 63.13 ± 2.75, respectively) and GST stages (87.97 ± 49.48 and 73.57 ± 4.61) compared to the control group (Nrf2: 54.1 ± 1.0; GST: 68.93 ± 2.28). The nanopolyherbal formulation also significantly decreased AGE itemion (1%: 1075.67 ± 107.51; 3%: 813.33 ± 117.05) compared to the control (1497.33 ± 161.58). These outcomes reveal that the nanopolyherbal formulation enhances antioxidant activity and inhibits glycation in PBMCs, suggesting its capability for managing oxidative stress-related condition.